Dampak Mediasi Komitmen Profesional Mempengaruhi Otonomi Kerja dan Kompetensi terhadap Job Engagement (Studi pada Pegawai Inspektorat Daerah Kabupaten Boven Digoel) - W.S. Agung Romadona (Journal of Management and Bussines (JOMB), 2024)
This research aims to determine the mediating influence of professional commitment in influencing work autonomy and competence on work engagement. The method used is a quantitative method. The data analysis method used is Partial Least Square (PLS) analysis. The research results showed that the work autonomy variable obtained P values > 0.05 (0.324 > 0.05) and t-statistics < 1.96 (0.987 < 1.96). The competency variable has a P value > 0.05 (0.818 > 0.05) and t-statistic < 1.96 (0.231 < 1.96). This value shows that work autonomy and competence do not have a positive and significant effect on work engagement. This research also proves that work autonomy does not have a positive and significant effect on professional commitment because it has a P value > 0.05 (0.449 > 0.05) and t-statistic < 1.96 (0.758 < 1.96). Competence has a positive and significant effect on professional commitment because it has P Values < 0.05 (0.000 < 0.05) and t-statistics > 1.96 (24.086 > 1.96). Keywords: Job Engagement, Competence, Mediation of Professional Commitment